Self-regulation at work.[article]. - Lord, Robert G.
Self-regulation at work conceived in terms of within-person processes that occur over time. These processes are proposed to occur within a hierarchical framework of negative feedback systems that operate at different levels of abstraction and with different time cycles. Negative feedback systems response to discrepancies in a manner that reduces deviations from standard (i.e., goals). This is in contrast to positive feedback systems in which discrepancies are created, which can lead to instability. We organize our discussion around four hierarchical levels -self, achievement task, lower-level task action, and knowledge/working memory. We theorize that these level are loosely connected by multiple constraints and that both automatic and more conscious processes are essential to self-regulation.Within-and cross -level affective and cognitive processes interact within the system to motivate goal-related behaviors while also accessing needed knowledge and protecting current intentions from interference. Complications common in the work setting(as well as other complex, real-life settings) such as the simultaneous pursuit of multiple goals, the importance of knowledge access and expertise, and team and multiperson processes are also discussed. Finally, we highlight the useful of the newest research methodologies and data-analytic techniques for examining such hierarchical, dynamic, within-person processes.